2015
DOI: 10.3389/fmed.2015.00026
|View full text |Cite|
|
Sign up to set email alerts
|

Escherichia coli Isolated from Urinary Tract Infections of Lebanese Patients between 2005 and 2012: Epidemiology and Profiles of Resistance

Abstract: The early treatment of urinary tract infections (UTIs) is directly related to decrease in morbidity, which makes the empirical treatment of great importance. Recently, beta lactamases of several types have emerged as significant mechanisms of resistance in Gram-negative bacilli, especially Escherichia coli. Our aim was to study the urinary E. coli isolated from Lebanese patients and to characterize their mechanisms of resistance. The study analyzed data between 2005 and 2012 of UTIs caused by E. coli. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 16 publications
6
30
1
2
Order By: Relevance
“…(8.2%). The results are in accordance with previous studies that identified the presence of the same species in 50–60% of these infections [19,20,21,22]. Other enterobacterial species such as Proteus spp., Enterobacter spp., Serratia marcescens , and Morganella morganii were recorded, as also revealed by other studies [23].…”
Section: Discussionsupporting
confidence: 93%
“…(8.2%). The results are in accordance with previous studies that identified the presence of the same species in 50–60% of these infections [19,20,21,22]. Other enterobacterial species such as Proteus spp., Enterobacter spp., Serratia marcescens , and Morganella morganii were recorded, as also revealed by other studies [23].…”
Section: Discussionsupporting
confidence: 93%
“…A study performed by Kateregga et al 2015, also reported that E. coli was the most common ESBL-producers (53.9 %) isolated from urine samples, followed by K. pneumoniae (28.7 %) [22]. The predominance of E. coli isolates from urine samples was in concordance with a study done in Lebanon by Daoud et al, 2015, which has compared between two periods of 2005 and 2012, and stated that ESBL-producing E. coli was isolated in 60.53% and 73.98%, while K. pneumoniae was isolated in 5.32% and 8.33 %, respectively [23].…”
Section: Discussionsupporting
confidence: 82%
“…The difference would be due to the sampling from different hospitals and from different geographic locations, whereas in our study, samples were collected only from two hospital setting. This study revealed that, out of the 37 E coli producing ESBL isolated from urine samples, the percentage of bla TEM was 73.0% followed by bla CTX-M (35.1%) and bla OXA-1 (8.1% (34). The genetic diversity of bla genes in isolates, suggested that resistance genes can easily move from one specie to another with the possibility of easy interspecies transfer.…”
Section: Table 4: Distribution Of Various Esbl Genes Combinations Accmentioning
confidence: 85%